Inductive Technologies of System-analytical Research as an Effective Tools in Complex Innovative Projects - Osypenko, V.V. (Індуктивне моделювання складних систем, 2012)
In this paper the some examples of the real system-analytic search direction projects of high complexity in different areas human activity are presented. The most problematic sides of modern technologies and their implementation have been formulated, in particular the high level of subjectivity in decisions making. Therefore, further improvement of the traditional information technologies and the development of new ones as well as the implementation of appropriate tools of such class of problems arise objectively as an acute problem of practice.